EU Charter of Fundamental Rights: What is the Legal Impact of Being Chartered? - Rufat R. Babayev (Romanian Journal of European Affairs)
This paper argues that the Charter of Fundamental Rights brought innovations not only by structuring the human rights mechanisms of the European Union, but also by improving the existing international legal mechanisms for the protection of the human rights. A comparative analysis between the Charter of Fundamental Rights and European Convention of Human Rights is also presented in the paper. Comparing these two legal texts, the paper aims to determine whether the Charter competes with ECHR, aims to replace it or merely complements it. The human rights clause of EU conditionality policy plays a crucial role in raising the level of human rights protection and democratic development in the candidate states.